If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + 5x = 60 Reorder the terms: 3 + x + 5x = 60 Combine like terms: x + 5x = 6x 3 + 6x = 60 Solving 3 + 6x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 60 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 60 + -3 6x = 60 + -3 Combine like terms: 60 + -3 = 57 6x = 57 Divide each side by '6'. x = 9.5 Simplifying x = 9.5
| -5(3x+-4)=-29+8x | | 1(x-3)= | | 7x-2=2x+48 | | -57-13x=-3(x-1) | | 30+23x=40x-14x | | f(2a)=16 | | 5+12x=-5+11x | | -29-a=6(-6+a) | | -5(3x-4)=-29 | | a+2a+7a= | | -x+9x=-63+17x | | -30=4x+2 | | 8x-6=2x+48 | | -69+37x=-17+16x+17x | | 9x/2-7=11 | | (6x+-19)+(3x+10)=180 | | 25n^6+40n^3+16=0 | | 6x^2+24x-9x+36=0 | | 3a+27=5a+98 | | 2(4-3x)=20-5x | | 12c^3+39c^2-36c= | | 3x-60=3 | | 8A=4x+4x | | -6n-12=-3(n+6) | | 0.4x+1.2=0.6x-0.2 | | D=v+0.5at | | 8=4c+4x | | 5r-6-r=-18 | | c^10-30c^5d^2+225d^4=0 | | 4(3x-9)-3=4(x-3)+13 | | 1+2n+1=14 | | y=4-3[0] |